HYDROLYSIS OF STARCH SACCHARIDES FROM SWEET POTATOES USING ENZYME - Risnoyatiningsih, Sri (Jurnal Teknik Kimia, 2011)
Glucose is a monosaccharide that is widely available in fruits, and plants obtained throughthe hydrolysis of starch saccharides using enzymes. Sweet potato starch hydrolysis is run by threeneckflask equipped with a stirrer. At stage Liquifikasi, three neck flask inserted into a solution ofstarch which has been set temperature and pH plus HCI and heated, then added α-amylase enzymein a certain time.Saccharification second stage, where the results liquifikasi cooled, set thetemperature and pH on certain conditions. Giukoamilase enzyme is then added to the volumeaccording to the specified variable, and incubated at a given time. At a certain time interval wastaken a few examples of the analyzed samples to be analyzed glucose levels. Process behaviorobserved in this study were changes in temperature, hydrolysis time and the addition of enzymes,the best hydrolysis results obtained at 60 0C, pH 4.5 and the addition of the enzyme glucoamylase,07 ml and the time hidrilisis 5 days with glucose levels reaching 5.65% and conversion yield of66.8% and 22.59%.Key words: Sweet Potato Starch, Liquifikasi, sakrifikasi, glucose